A Study on Human, Technical, and Environmental Factors Contributing to the Bell 505 Helicopter Accident in Bali Caused by a Kite String - Duta Fatila; Rizqi Maulana Firdaus; Delmio Ave Maria Guterres de Sousa (Politeknik Penerbangan Surabaya, 2026)
This study aims to examine the Bell 505 helicopter accident in Bali caused by a kite string by analyzing human, technical, and environmental contributing factors. The research employed a qualitative descriptive method through document analysis, including news reports, scientific literature, and aviation safety regulations. The findings indicate that the accident occurred due to limited airspace supervision, low public awareness regarding restrictions on kite activities within the Airport Safety Zone (KKOP), and the absence of effective risk mitigation and communication systems among aviation authorities and operators. This research contributes to aviation safety science by emphasizing the importance of public education, strengthened regulatory enforcement, and improved risk management in helicopter operations, particularly in tourism areas with high environmental interference potential.